Effects of Antioxidants and Flavonoids of Sea Buckthorn on Skin Whitening and Skin Erythema - Ali Khan, Barkat; Akhtar, Naveed; Mahmood, Tariq; M. Shoaib, Haji; Qayum, Mughal; Saeed, Tariq (Asian Journal of Chemistry, 2010)
The aim of this study is to determine the effects of newly formulated W/O emulsion (cream) of Sea Buckthorn versus its vehicle (base) as control on skin melanin and skin erythema. Sea Buckthorn extract was entrapped in w/o emulsion. The newly formulated base and formulation (containing 1 % concentrated extarct of Sea Buckthorn) were applied to the cheeks of 21 healthy human volunteers for 8 weeks. The base showed insignificant (p > 0.05) effects while the formulation showed statistically significant (p £ 0.05) decrease in skin melanin content. Skin erythema was significantly (p £ 0.05) reduced by the formulation.